Author Correction: The origin of Rhinocerotoidea and phylogeny of Ceratomorpha (Mammalia, Perissodactyla) - Bin Bai (Communications Biology, 2021)
A Correction to this paper has been published: https://doi.org/10.1038/s42003-021-01660-x.